Osmanlı Diplomasisinde “Musalahalar Devletler İledür” Kaidesi - Hilal ÇİFTÇİ (Gazi Akademik Bakış)
It is not possible to think of the experience of the Ottoman Empire in the field of Diplomacy apart from her adventure in the field of politics. Just as her political adventure was in a unique way, her experience in the field of diplomacy was likewise unique. The Ottoman Empire’s diplomatic activities through permanent representatives in foreign countries coincided with a late date like 1793. However, this does not mean that the Ottoman had not carried out any diplomatic activity before this time. For while the sultans of the founding period used the diplomacy as a tool to consolidate and enhance their political achievements, the sultans of the ascension period used the diplomacy as an indicator and a manifestation of their political forces. In the period when the state was weakened and fell out of power, instead of being the party determining the rules of diplomacy, she continued her existence with the diplomatic balance policy as a part of European States law. In other words, although the diplomacy was carried out in different ways with different missions, it had always been an instrument applied in the relations of the Ottoman Empire with other states from her foundation to her collapse. In doing so, the Ottoman Empire, especially in her politically strong times, adopted a set of principles of diplomacy which both meticulously applied by herself and accepted by her counterparts. The subject of our study, the principle of “treaties are between states” is one of these principles. In our study, we will try to put forth the diplomatic background of this principle and how it is carefully applied by the Ottoman Empire.